SOSIALISASI OLAHRAGA PERMAINAN BOLA SUNDUL DI KOTA SAMARINDA - Muhammad Rifai; Didik Cahyono; Hendry Ismawan; Paryadi Paryadi (Yayasan Education and Social Center, 2022)
East Kalimantan is hosting a national event in the form of the National Recreational Sports Festival (FORNAS) in 2019. And the sundul ball game becomes one of the games that will be contested in the event. While the people of East Kalimantan itself are not all familiar with this sport. The agreement of this socialization is as follows: (1) Memasyarakatkan and preserve the traditional game native to Indonesia, (2) Menyiapkan teachers and students as coaches in the game of sundul ball in East Kalimantan and (3) Menyiapkan Athletes of sundul ball games to represent East Kalimantan at the National Recreational Sports Festival (FORNAS) event. The method used is socialization by way of theory and practice, regarding game equipment, how to play, rules and basic techniques of playing sundul ball. This activity runs smoothly and in accordance with the program that has been planned. Held at FKIP Unmul Campus (for materials) and on the sempaja stadium volleyball court. Participants attended as many as 25 people consisting of teachers and students majoring in sports. This activity received high appreciation from participants by being characterized by the enthusiasm and spirit of participants in following the socialization of the game given from the beginning to the end of the activity. The existence of this socialization community becomes aware of how to play this game in accordance with its rules and get athletes to represent east Kalimantan at the FORNAS event that will be held in east Kalimantan.